FRACTAL-STATISTICAL ANALYSIS OF WATER LEVEL FLUCTUATION FOR THE TRUBIZH RIVER - Борисенко, Є. Г.; Гроза, В. А.; Лещинський, О. Л. (Science-based technologies, 2014)
The problem of hydrological-ecological state of Dniper’s left tributary — the Trubizh river is formulated. The water object jas been considered as a complicated dynamic system. Water levels in the river have been considered as the main indicators of dynamics (daily data for period from 1982 to 2012 from archive of Central geophysical Observatory) that have been averaged, minimized and maximized for month. The choice of investigation method have been scientifically grounded. The methodology of fractal-statistical analysis has been represented. The R/S and quasi-cyclical analysis of water level indicators for the Trubizh river has been carried out (Hurst exponents have been calculated, phase space has been constructed, quasi-cycles have been extracted and grouped). As a result of water level dynamics investigation authors have proposed an interval of hydrological state repetition. On the basis of obtained qualitative and quantitative characteristics of fractal statistics, the persistent character of time series, memory and quasi-cycles existence have been proved. A possibility of fractal statistics methods application to studying and forecasting of other ecological processes has been grounded.